Helium and neon isotopes in São Miguel island basalts, Azores Archipelago: New constraints on the “low 3He” hotspot origin - Moreira, Manuel (2012)
Lavas from the São Miguel Island, Azores Archipelago, have peculiar isotopic compositions, including radiogenic lead and strontium and un-radiogenic neodymium. The peculiar isotopic trend of São Miguel is evident in the lead-lead diagram where both 207Pb/204Pb and 208Pb/204Pb ratios are high for a given 206Pb/204Pb ratio compared to other oceanic island basalts. This signature is unique among OIBs and is particularly evident in the Nordeste area, the oldest part of São Miguel island (≥1 Ma). Only a few olivine samples from the Nordeste volcanic complex have been analyzed for helium. They show radiogenic helium signatures with 4He/3He up to 174,000 (R/Ra ~4) [Moreira et al., Helium and lead isotope geochemistry in the Azores archipelago, Earth Planet. Sci. Lett. 169: 189–205, 1999]. However, because the Nordeste volcano has an age between 1 and 4 Ma and because these samples have low helium concentrations, these radiogenic helium isotopic ratios must be considered with caution as they can also reflect post eruptive radiogenic production. In this paper we present a detailed study of the helium and neon isotopic ratios obtained from 17 Nordeste samples in order to better constrain the helium isotopic signature of the São Miguel mantle source. By coupling helium and the other isotopic systems, we propose that the São Miguel source contains non-degassed material, enriched in U and Th, that was stored in the mantle for the last ~3 Ga. As suggested by Elliot et al. [Elliott et al., The origin of enriched mantle beneath São Miguel, Azores, Geochim. Cosmochim. Acta 71: 219–240, 2007], underplated magma intruded into oceanic lithosphere and subducted ~3 Ga ago is a possible explanation for the peculiar São Miguel source isotopic signatures.